High-speed pre-clinical brain imaging using pulsed laser diode based photoacoustic tomography (PLD-PAT) system - Upputuri, Paul Kumar (2016)
Photoacoustic tomography (PAT) is a promising biomedical imaging modality for small animal imaging, breast cancer imaging, monitoring of vascularisation, tumor angiogenesis, blood oxygenation, total haemoglobin concentration etc. The existing PAT systems that uses Q-switched Nd:YAG and OPO nanosecond lasers have limitations in clinical applications because they are expensive, non-potable and not suitable for real-time imaging due to their low pulse repetition rate. Low-energy pulsed near-infrared diode laser which are low-cost, compact, and light-weight (<200 grams), can be used as an alternate. In this work, we present a photoacoustic tomography system with a pulsed laser diode (PLD) that can nanosecond pulses with pulse energy 1.3 mJ/pulse at ~803 nm wavelength and 7000 Hz repetition rate. The PLD is integrated inside a single-detector circular scanning geometric system. To verify the high speed imaging capabilities of the PLD-PAT system, we performed in vivo experimental results on small animal brain imaging using this system. The proposed system is portable, low-cost and can provide real-time imaging.